Daya Dukung Kesiapan E Retribusi Pasar Blambangan Kabupaten Banyuwangi (Supporting Capacity of E Retribution Readiness in Blambangan Market Banyuwangi Regency) - Novitasari, Dessy; Hidayat, Rachmat; Azhari, Abdul Kholiq (University of Jember, 2019)
AbstractThis study aims to describe the supporting capacity of E Retribution readiness in Blambangan Market. This research was based on the existingrenewal information technology with the development of e Government regarding the acceptance and collection of electronic market retribution or Market E Retribution. It is held by the Department of Industry and Trade of Banyuwangi Regency in collaboration with PT Bank Jatim as a facilitator of supporting infrastructure for the implementation of Market E Retribution. To know about the readiness of implementing E Market Retribution, there are three elements of e Government success in implementing Market E Retribution, namely support, capacity, and value. Therefore, this descriptive study employed a qualitative approach. Research data were collected through observation, documentation, and interview. The informants were determined purposively. To test data validity, researchers used triangulation technique. Then, the data were analyzed by systematically compiling data obtained from interview, field note, and other sources; so that, the data were easily understood and the findings can be informed to the people. The findings indicated that the readiness of E Retribution implementation in Blambangan market was shown from some elements. Support element as the first element produced the implementation of the Market E Retribution policy through the collaboration of the Department of Industry and Trade with PT Bank Jatim. The second element was capacity. It produced the infrastructure used in the implementation ofMarket E Retribution. The transaction tool used was an EDC (Electronic Data Capture) machine. The final element was value which wasin the form of evaluation on the MarketE Retribution program by traders to the implementer of Market E Retribution. The usefulness value of E Retribution in Blambangan Market changed the mindset of traders regarding the ease of information technology in public services. Moreover, it could be felt directly such as in the implementation of E Market Retribution. The value obtained in the presence of this Market E Retribution was certainty. Count certainty, deposit certainty, and merchant certainty in receiving the retribution were e Government based services.Keywords: supporting capacity, e government, market e retribution